Nanoparticles as potential hallmarks of drought stress tolerance in plants. Issue 2 (20th April 2022) - Kandhol, Nidhi; Jain, Mukesh; Tripathi, Durgesh Kumar
Abstract: Plants are inevitably exposed to drought stress limiting their growth and causing yield loss, thus inciting food crises across the world. Nanoparticles (NPs) are regarded as effective and promising tools for modulation of crop yield to overcome current and future constraints in sustainable agricultural production by upgrading the plant tolerance mechanism under abiotic stress conditions, including drought. NPs exhibit alleviating effects against drought stress via induction of physiological and biochemical readjustments accompanied by modulation of gene expression involved in drought response/tolerance. NPs ameliorate drought‐induced reduction in carbon assimilation via increasing the photosynthetic activity. The improved root growth, upregulation of aquaporins, modification of intracellular water metabolism, accumulation of compatible solutes and ion homeostasis are the major mechanisms used by NPs to mitigate the osmotic stress caused by water deficit. NPs reduce water loss from leaves through stomatal closure due to fostered abscisic acid (ABA) accumulation and ameliorate oxidative stress damage by reducing reactive oxygen species and activating the antioxidant defense system. This review provides an evolutionary foundation regarding drought stress in plant life and summarizes the interactions between NPs and plants under drought. The subsequent impact of NPs on plant development and productivity and recent nanobiotechnological approaches to improve drought stress resilience are presented. On the whole, this review highlights the significance of NPs in dealing with the global problem of water scarcity faced by farmers.